2021
DOI: 10.1515/ijeeps-2021-0241
|View full text |Cite
|
Sign up to set email alerts
|

Improvements in deviation settlement mechanism of Indian electricity grid system through demand response management

Abstract: This paper proposes the improvements in deviation settlement mechanism of Indian electricity grid system through demand response management (DRM) with the objective to minimize real-time under-injection/over-drawl or maximize real-time over-injection/under-drawl with respect to scheduled injection/drawl such that the deviation settlement charge (DSC) is minimum, subject to the network power flow equations, transmission line capability constraints, DRM constraints and bounds on variables. The mechanism to settl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Their case study demonstrated that setting a penalty price for deviations can suppress market volatility and consistently yield a non-negative market surplus. Bharti et al suggested that in the Indian power grid system, both excess and insufficient DE from planned transactions could be managed by penalties and incentive payments to stabilize grid frequency [17]. Reinier et al examined the impact of DE pricing mechanisms on market balance in the European market, analyzing six alternative pricing mechanisms based on an Agent model, with the single pricing mechanism resulting in the lowest deviation costs [18].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Their case study demonstrated that setting a penalty price for deviations can suppress market volatility and consistently yield a non-negative market surplus. Bharti et al suggested that in the Indian power grid system, both excess and insufficient DE from planned transactions could be managed by penalties and incentive payments to stabilize grid frequency [17]. Reinier et al examined the impact of DE pricing mechanisms on market balance in the European market, analyzing six alternative pricing mechanisms based on an Agent model, with the single pricing mechanism resulting in the lowest deviation costs [18].…”
Section: Literature Reviewmentioning
confidence: 99%